Natural Gas Dehydration Optimization - Mohd Ghazali, Mohd Fahdi (Universiti Teknologi PETRONAS, 2010)
Natural Gas is a vital component of the world's supply of energy. It is one of the deilfiest, safest, and most useful of all energy soutees. Undet normal production conditions, it saturated with water vapor. Water vapor increases natural gas corrosivity especially when acid gases are present. This report discusses the research done and basic understanding of the chosen topic, which is natural gas dehydration optimization. The objectives of this project are to do the comparison between different types of Natural Gas dehydration technology on the basis of efficiency and capacity and to do the simulation to optimize operating condition of gas dehydration technology. The current technologies used to dehydrating gas have some weaknesses in term of efficiency, capacity, cost effectiveness and are harmful to environment M for this study, gas dehydration using solid desiccant is being considered. It is a common technology used widely in the world especially in oil and gas industries. In order to optimize this technology, a simulation model base on the actual dehydration unit in the liquefied natural gas (LNG) plant is used. The optimization is base on manipulating temperature and pressure to see the effect to the adsorption capacity and later, from the manipUlated pressure, the hydrate fOrmation temperature can be predicted. From this, the optimum temperature and pressure of operating the dehydration unit can be known. Furthermore, a study of increasing the moisture removal by adding pre-dehydration unit is also discussed in this study.